The Ribbon and the Rose : Visual Rhetorics Against Violence to Women - Goldrick-Jones, Amanda (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2004)
AbstractAfter the December 6, 1989 massacre of fourteen young women at Montréal’s École Polytechnique, Canadian women’s anti-violence groups and a now international men’s campaign against men’s violence to women adopted a variety of resonant visual images in commemoration and protest. The striking differences underlying women’s and men’s choices of images also reflect tensions at a rhetorical level about the appropriateness of men speaking out against violence to women. To explore these tensions, this article uses a method of rhetorical analysis that maps associations among “men’s” and “women’s” images, situates these associations within particular social contexts, and suggests some possible effects of these images and their messages on various audiences. While some activists feared that the men’s white ribbon — rather than the women’s rose or other symbols — might dominate the public imagination as a generalized protest against violence to women, a brief joint billboard campaign displaying the white ribbon and the rose side by side represents the possibility of women and men working with and through the power inequalities that exacerbate gender differences.